ASK-CDM-ECTS: A tool for facilitating common european university course description towards higher education integration - Sampson, Demetrios; Zervas, P.; Limnatitis, R. (2009)
In this paper, we present ASK-CDM-ECTS, a web based authoring environment for describing higher education study programmes and courses, as well as, their educational material, following an application profile of the Course Description Metadata Specification (CDM), namely, CDM-ECTS, that supports the specific requirements of the European Credit Transfer and Accumulation System (ECTS). © 2009 IEEE.